Simultaneous Interpreting and AI Text-Mediated Output: A Comparative Analysis of English–Greek Institutional Discourse - Ioannidis, Anastasios (International Journal of Language, Translation and Intercultural Communication, 2026)
This study investigates how closely AI-based text-mediated output approximates professional human simultaneous interpreting with respect to target-language output characteristics in a high-stakes institutional context. Using three plenary speeches from the European Parliament, it compares official Greek simultaneous interpretation with AI-generated Greek output produced via a neural machine translation system. The analysis combines proposition-level error annotation with qualitative discourse-oriented analysis. While the AI output displays fewer overall errors, it shows systematic limitations in pragmatic appropriateness, evaluative intensity, terminology, and stylistic naturalness. Human interpreting, by contrast, demonstrates greater sensitivity to contextual cues and audience-oriented reformulation, despite strategic information compression.